Evaluasi Pembelajaran Pendidikan Agama Islam Pada Mata Pelajaran Al-Qur’an Hadis Di MAN 1 Plus Keterampilan Bengkalis - Muhammad Muhyidin; Naufal Fajri Rangga; Agus Setioso; Siti Khairiah (Universitas Pakuan, 2026)
EVALUATION OF ISLAMIC RELIGIOUS EDUCATION LEARNING IN THE QUR'AN AND HADITH SUBJECT AT MAN 1 PLUS SKILLS BENGKALIS Evaluation in the teaching and learning process is crucial in education because it measures the extent to which students have achieved the learning objectives. This study aims to examine how evaluation of Islamic religious learning is implemented in the Al-Quran and Hadith subject at MAN 1 Plus Kebudayaan Bengkalis. This study will cover the evaluation methods, the types and tools used by teachers to measure students' cognitive abilities, attitudes, and skills, and the challenges teachers encounter during assessment. The approach chosen for this study is qualitative with a descriptive approach. Data were collected through direct observation and conversations with Al-Quran and Hadith teachers and students in grade 11. Data analysis included data simplification, presentation, and drawing conclusions. The study findings indicate that the assessment of the Al-Quran and Hadith subject has been carried out comprehensively, encompassing cognitive, affective, and psychomotor aspects. Teachers use various assessment methods, such as written questions, oral questions and answers, behavioral observations, discussion forums, demonstrations of Quranic reading skills, and memorization tests of verses and hadith. In addition, teachers also provide remedial programs for students who have not yet achieved their learning objectives. The obstacles faced by teachers during the evaluation process are differences in abilities between students, limited learning time, and difficulties in managing students during learning activities.